First family - Baldacci, David (New York : Grand Central Pub., 2009)
A daring kidnapping turns a children's birthday party at Camp David into a national security nightmare, pushing agents Sean King and Michelle Maxwell to their limits.
Keywords: King, Sean (Fictitious character) -- Fiction; Maxwell, Michelle (Fictitious character) -- Fiction; Kidnapping -- Fiction; National security -- Fiction; Suspense fiction